A general autocatalytic route toward silica nanospheres with ultrasmall sized and well-dispersed metal oxide nanoparticles. Issue 20 (16th May 2018) - Xu, Linxu; Cui, Fang; Zhang, Jiajia; Zhang, Xiao; Wang, Yan; Cui, Tieyu
Abstract : Metal ions@silica nanospheres were prepared by our presented intramolecular autocatalytic route under neutral condition without any additional catalysts and their converse to mNPs@silica nanocomposites. Abstract : A facile and efficient approach for the synthesis of metal ions@silica nanospheres is proposed by using an intramolecular autocatalytic route. By the rational selection of reactants, metal ions@silica nanospheres can be obtained via successive spontaneous reactions under near neutral conditions. After thermal treatment, spherical silica equipped with ultrasmall and highly dispersed metal oxides nanoparticles was obtained.